(untitled) (Fiep Bulletin - online, 2014)
The major specificity of workstations, the increasing noise pollution in several environments, the intensification of repetitive movements, among others are some challenges that ergonomics is currently facing, and, regarding the civil construction sector, there are many tangible improvements to be made in order to solve those issues that appear at the building site and are observed through workers’ muscular pains, fatigue and discomfort complaints during the execution of their daily activities or afterwards. Therefore, basing on this premise and relying on the legal concepts related to environmental comfort and biomechanics, this article’s objective consists on an ergonomic analysis of three distinct workstations at the same building site in the city of Curitiba: the mortar preparation using a mixer, the cut and laying of tiles over floors and the soil compaction through the use of a percussion compactor. The results presented worrying factors on those activities, such as the high noise intensity level the workers are exposed to, and also positive aspects, like the adequate amount of work breaks the employee has during his workday. Lastly, some suggestions were made for coherent alternatives to each workstation with the purpose of developing a more ergonomic way of completing the tasks that caused stress among workers.